2001
DOI: 10.1086/323762
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Colonization with Vancomycin‐ResistantEnterococcus faeciumin Long‐Term Care Patients and the Significance of “Clearance”

Abstract: Little is known about the persistence of colonization with vancomycin-resistant Enterococcus faecium (VRE) in the nononcologic, non-intensive care unit patient. We studied all patients who had VRE isolated on > or =2 occasions of > 1 year apart (Study A) and those who had been "cleared" of VRE colonization after 3 negative stool cultures (Study B). Twelve patients had stored VRE isolates recovered > 1 year apart (Study A), and 58% of paired isolates were genotypically related according to pulsed field gel elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
1
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 39 publications
4
38
1
2
Order By: Relevance
“…20 One institution, which defined VRE clearance as 3 negative stool cultures more than 3 weeks apart, found in subsequent, prospective surveillance testing that VRE recolonization occurred in 5 of 21 patients (24%) who had "cleared." 14 The same authors identified 12 patients who had at least 2 VRE-positive cultures more than 1 year apart, supporting concern for prolonged colonization. 14 Donskey et al 15 demonstrated that individuals who had cleared VRE colonization with 3 negative stool cultures collected at least 1 week apart had a high recurrence rate (62%) if they were exposed to antibiotics in the following year.…”
Section: Vancomycin-resistant Enterococcus (Vre)mentioning
confidence: 90%
See 3 more Smart Citations
“…20 One institution, which defined VRE clearance as 3 negative stool cultures more than 3 weeks apart, found in subsequent, prospective surveillance testing that VRE recolonization occurred in 5 of 21 patients (24%) who had "cleared." 14 The same authors identified 12 patients who had at least 2 VRE-positive cultures more than 1 year apart, supporting concern for prolonged colonization. 14 Donskey et al 15 demonstrated that individuals who had cleared VRE colonization with 3 negative stool cultures collected at least 1 week apart had a high recurrence rate (62%) if they were exposed to antibiotics in the following year.…”
Section: Vancomycin-resistant Enterococcus (Vre)mentioning
confidence: 90%
“…14 The same authors identified 12 patients who had at least 2 VRE-positive cultures more than 1 year apart, supporting concern for prolonged colonization. 14 Donskey et al 15 demonstrated that individuals who had cleared VRE colonization with 3 negative stool cultures collected at least 1 week apart had a high recurrence rate (62%) if they were exposed to antibiotics in the following year. Individuals with risk factors for VRE colonization have demonstrated recurrence, 16 and recent studies suggest that a strategy of 3 weekly consecutive surveillance cultures to identify VRE clearance results in recurrence rates of 11%.…”
Section: Vancomycin-resistant Enterococcus (Vre)mentioning
confidence: 90%
See 2 more Smart Citations
“…are part of the gastrointestinal microbiota, supercolonization by resistant strains can occur with relative ease 4 . The limited current evidence suggests that patients colonized with VRE cannot be colonized by nonresistant strains 5,6 . The contamination of the hospital environment and the ability of enterococci to survive outside the human body for prolonged periods are factors for the occurrence of cross-contamination, either through the hands of health care workers, equipment, or surfaces 7 .…”
Section: Introductionmentioning
confidence: 95%